Zakres działania systemu informacji marketingowych w przedsiębiorstwie eksportującym - Malinowski, Andrzej (Wydział Prawa i Administracji UAM, 1978)
The most difficult phase of works on a concept of marketing information system is determination of information needs existing in an exporting enterprise. The knowledge of information needs of an enterprise is in turn of fundamental importance for determination of the scope of tasks for the system, its organization, methods, forms and technics of performance. This knowledge determines moreover efficiency of system's functioning. In the article after accomplished analysis the needs of an exporting enterprise have been presented in the form of an information network, combined of decision nodes and information linkages, connecting the nodes in the unity. Presented decision nodes do not answer the organizational division of an enterprise but its functional division. Thanks to such solution the possibilities exist to determine which information is needed for realization of individual tasks resulting from the management system accepted toy Polish exporting enterprises. Determination of needs in the sphere of marketing information enables to settle the basic system functions fulfilled by an exporting enterprise. These functions result from the essence of marketing information and they are also conditioned by its contents and character in the process of undertaking management decisions. Forecasting, deciding (the aid in taking up management decisions), controlling and informing (systematic distribution of plan marketing information in an enterprise) belong to them. The accomplished survey of basic functions of the marketing information system enables to define their features and relationships existing among them. The optimal solution of the system should consider simultaneous and equal realization of all functions. Achievement of this goal is very difficult in practice and the causes influencing the situation have not been examined yet.
The Scope of Influence of Marketing Information System in an Exporting Enterprise
Keywords: WPiA